Financial Literacy and Financial Behavior on Investment Decisions: Lampung Investors - Winda Rika Lestari; Yosua Theo Herlia; Lukmanul Hakim (Proceeding International Conference on Information Technology and Business, 2022)
This study aims to analyze financial literacy and financial behavioral factors that affect investment decisions for investors in Lampung. This study will focus on investors in Lampung with more than one year of investment experience. The data used is primary data collected through online questionnaires. While the method used is a quantitative method with multiple linear regression approach. This study uses the Investment Decision variable as the dependent variable, while the independent variable consists of Financial Literacy, Herding, and Risk Tolerance. The results of this study indicate that financial literacy, risk tolerance, and herding have a significant effect on investment decisions. This means that investors tend to accept information and follow the decisions of others, where the greater the financial literacy, herding, and risk tolerance factors, the better the investor's decisions will be.Keywords: Investment Decision, Financial Literacy, Risk Tolerance, Herding